Prevalence of tobacco use, exposure to secondhand smoke and knowledge on smoking cessation among students of health professions in Central Greece: a cross-sectional study. Issue 10 (21st October 2020) - Samara, Athina A; Rachiotis, George; Pettemeridou, Sofia; Papastamatiou, Konstantinos; Tourlakopoulos, Konstantinos; Chelioti, Eythimia; Katsioulis, Antonis; Hadjichristodoulou, Christos S
Abstract : Objectives: The aim of this study was to assess the prevalence of tobacco use and exposure to secondhand smoke among students of health professions (SHPs) and determine possible risk factors for current smoking. In addition, we sought to investigate the level of students' knowledge regarding smoking cessation. Design: Cross-sectional. Setting: Central Greece. Participants: A convenient sample of 822 SHP volunteers were used, composed of 365 medical students, 123 students from a biochemistry department, 71 students from a nursing department, 176 from medical laboratory department and 84 students from a veterinary medicine department. Primary and secondary outcome measures: We investigated the prevalence of current smoking and secondhand smoke, their determinants and SHP's knowledge and attitudes regarding smoking cessation. Univariate and logistic regression statistical analysis were used in order to identify risk factors associated with current smoking. Results: The prevalence of current smoking was estimated at 23.5% (95% CI 20.7% to 26.5%), while 49% of current smokers reported they wanted to quit smoking. The prevalence of current e-cigarette use was 1.2%. In addition, 96.5% (95% CI 94.9% to 97.5%) of SHP have been exposed to secondhand smoke at least 1 day per week. Logistic regression analysis showed that increasing age (p<0.001), alcohol consumption (p<0.001) and exposure to secondhand smoke in the home (p<0.001) were independent risk factors for current smoking. Notably, only 11.6% of the participants had learnt about methods to be used for smoking cessation. Conclusions: Our results underline the need for integrated tobacco control initiatives that should discourage tobacco use among SHP, promote smoke free schools of health science, and implement programs that train SHP in effective cessation-counseling techniques.